Deferred treatment with sofosbuvir–velpatasvir–voxilaprevir for patients with chronic hepatitis C virus who were previously treated with an NS5A inhibitor: an open-label substudy of POLARIS-1. (August 2018) - Bourlière, Marc; Gordon, Stuart C; Schiff, Eugene R; Tran, Tram T; Ravendhran, Natarajan; Landis, Charles S; Hyland, Robert H; Stamm, Luisa M; Zhang, Jie; Dvory-Sobol, Hadas; Subramanian, G Mani; Brainard, Diana M; et al.
Summary: Background: Direct-acting antiviral regimens containing NS5A inhibitors are highly effective treatments for chronic hepatitis C virus (HCV) infection, but are not always successful. In the POLARIS-1 phase 3 study, sofosbuvir-velpatasvir-voxilaprevir for 12 weeks was highly effective in the treatment of chronic HCV infection in patients previously treated with a direct-acting antiviral regimen containing an NS5A inhibitor. We aimed to assess the efficacy and safety of sofosbuvir-velpatasvir-voxilaprevir in patients from the deferred treatment group of POLARIS-1, who were initially assigned to masked placebo treatment. Methods: This open-label, deferred treatment substudy was done at 73 clinical sites (hospitals and clinics) in the USA, France, Canada, the UK, Germany, Australia, and New Zealand. Patients who received placebo in the primary study and who did not have a new clinically significant illness at the post-treatment week 4 assessment were eligible to enter this substudy. Participants received a combination tablet of sofosbuvir (400 mg), velpatasvir (100 mg), and voxilaprevir (100 mg) once daily for 12 weeks. The primary efficacy outcome was achievement of sustained virological response (defined as HCV RNA concentration below the lower limit of quantification) 12 weeks after the end of treatment (SVR12). The primary safety outcome was the proportion of patients who discontinued treatment due to adverse events. This study is registered withClinicalTrials.gov, numberNCT02607735, and the EU Clinical Trials Register, number 2015-003455-21. Findings: 152 patients received placebo in the primary study and were potentially eligible for participation in the open-label substudy, of whom 147 were enrolled from March 30, 2016, to Oct 12, 2016. All 147 patients completed treatment, and 143 (97%; 95% CI 93–99) achieved SVR12. Four (3%) patients had virological relapse; all had HCV genotype 1a infection and one also had compensated cirrhosis. The most common adverse events were fatigue (31 [21%]), headache (29 [20%]), diarrhoea (28 [19%]), and nausea (21 [14%]). No deaths, treatment discontinuations, or treatment-related serious adverse events occurred. Interpretation: Supporting the results from the blinded portion of the phase 3 primary study, the single-tablet regimen of sofosbuvir-velpatasvir-voxilaprevir for 12 weeks was safe, well tolerated, and highly effective in patients with chronic HCV infection who had previous treatment failure with NS5A inhibitor-containing regimens. A salvage regimen for this population represents an important advance for patients with limited retreatment options. Funding: Gilead Sciences.